Prevalence and Risk Profile Of Unread Messages To Patients In A Patient Web Portal - Crotty, B.H.; Mostaghimi, A.; O’Brien, J.; Bajracharya, A.; Safran, C.; Landon, B.E. (Applied Clinical Informatics, 2015)
Background: Excitement around the adoption of electronic communication between physicians and patients is tempered by the possibility of increased clinical and legal risk. If patients do not read messages in a timely fashion, duplicative communication efforts may be required and patient safety may be jeopardized.Objective: We sought to assess the prevalence and risk profile of unread messages in a mature patient portal.Methods: We analyzed six years of messages (2005–2010) from physicians to patients to determine the prevalence and associated characteristics of unread messages in a patient portal. We focused on clinical messages, and excluded announcements. Because some physicians sent clinical messages to groups of patients, we labeled messages sent to more than 5 patients as “outreach” messages and excluded them from general analyses. We performed a chart review of 75 clinical messages to assess for harm.Results: We found that 3% of clinical messages were unread after 21 days. Messages arriving outside of business hours were slightly more likely to go unread (RR 1.15 95% CI 1.11–1.19). Patients who were male (OR 1.14 CI 1.04–1.26) African American (OR 1.69 CI 1.29–2.22) or Hispanic (OR 1.74 CI 1.17–2.59), or in the lowest income group (OR 1.72 CI 1.19–2.49) were more likely to have unread messages. Chart review showed no evidence of harm, but 13% of sampled unread messages were associated with potential delays in care. Incidentally, we found 50% of the physician-initiated outreach messages were unread.Conclusions: Overall, secure messaging appears a safe form of communication, but systems to notify senders when messages are unread may have value. While most clinical messages were read, many outreach messages were not, providing caution for relying on such systems for information dissemination. Similar to other studies, differences by race and income were observed and require further study.Citation: Crotty BH, Mostaghimi A, O’Brien J, Bajracharya A, Safran C, Landon B. Prevalence and Risk Profile Of Unread Messages To Patients In A Patient Web Portal. Appl Clin Inf 2015; 6: 375–382http://dx.doi.org/10.4338/ACI-2015-01-CR-0006
Keywords: Personal health records; email; communication; secure messaging; electronic health records